2012
DOI: 10.1021/ic300993a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemistry of Organometallic Cobaltadithiaazulenes

Abstract: Reaction of tropolone or hinokitiol with phosphorus pentasulfide (P(2)S(5)) directly gives the sulfurized precursor [PS(2)(SST)](2) or [PS(2)(SSH)](2) (SST = dithiotropolonato or SSH = dithiohinokitiolato). The resulting [PS(2)(SST)](2) or [PS(2)(SSH)](2) is further reacted with [CpCoI(2)(CO)] (Cp = η(5)-cyclopentadienyl) to form the organometallic [CpCo(I)(SST)] (1) or [CpCo(I)(SSH)] (2), respectively. 1 and 2 have a cobaltadithiaazulene ring containing one cobalt and two sulfur atoms in the five-membered rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The electronic communication between the π orbital of a dithiolate ligand and the d orbital of a metal ion produces quasi-aromaticity, the delocalization of π electrons over the metalladithiolene ring. The unsaturated metal center results in redox activity, photofunction, and chemical reactivity, providing an interesting motif for CONASHs. π-Conjugated multinuclear metalladithiolene systems allow very strong electronic communication among the metal centers, and their electronic structures can be easily controlled by changing the metal centers.…”
Section: Metalladithiolene Conashsmentioning
confidence: 99%
“…The electronic communication between the π orbital of a dithiolate ligand and the d orbital of a metal ion produces quasi-aromaticity, the delocalization of π electrons over the metalladithiolene ring. The unsaturated metal center results in redox activity, photofunction, and chemical reactivity, providing an interesting motif for CONASHs. π-Conjugated multinuclear metalladithiolene systems allow very strong electronic communication among the metal centers, and their electronic structures can be easily controlled by changing the metal centers.…”
Section: Metalladithiolene Conashsmentioning
confidence: 99%
“…In the former view, Htrop and its derivatives have been mainly investigated in terms of the antioxidant properties such as the inhibition of various oxidases. In the latter sense, Htrop derivatives have attracted attention as a framework for organic redox systems, ever since Nozoe proposed tropoquinone (cyclohepta-3,6-diene-1,2,5-trione) as an oxidized form of 5-hydroxytropolone . The redox chemistry of metal tropolonate complexes has been also investigated, including the study of Htrop derivatives as redox-active ligands, while ruthenium tropolonate complexes have not been fully investigated. Even a basic cyclic voltammetry (CV) study of [Ru­(trop) 3 ] ( 1 ) had not been reported until our recent report .…”
Section: Introductionmentioning
confidence: 99%